1997
DOI: 10.1002/phbl.19970530305
|View full text |Cite
|
Sign up to set email alerts
|

Röntgen‐Mikrotomographie

Abstract: Abb. 1: Durch Rontgen-Mikrotomographie bei einer Wellenlange von ca. 70 pm gewonnenes Bild eines Mikrokallus (netzsrtiges Knochengebilde in der Bildmitte). Die Knochenprobe wurde durch eine Biopsie vom Beckenkamm eines an renaler Osteopathie (nierenbedingter Knochenkrankheit) erkrankten Patienten entnommen. Die Folge der Erkrankung sind ubergrofie Hohlraume, verdunnte, unterbrochene oder fehlende Stutzelemente (Trabekeln). Das netzartige Knochengebilde ist vermutlich die Reaktion des Organismus auf Mikrofraktu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Micro-CT is a powerful technique that allows visualization of the internal structure of opaque objects without destroying the sample. As with synchrotron illumination (Bonse 1997), micro-CT with laboratory polychromatic x-ray sources already has several applications in bone research (Elliott et al 1997, Stenstrom et al 2000, Ruegsegger et al 1976. The overall bone quality is determined by its structural and material properties, such as bone mass, geometry, architecture and composition of the bone (Einhorn 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Micro-CT is a powerful technique that allows visualization of the internal structure of opaque objects without destroying the sample. As with synchrotron illumination (Bonse 1997), micro-CT with laboratory polychromatic x-ray sources already has several applications in bone research (Elliott et al 1997, Stenstrom et al 2000, Ruegsegger et al 1976. The overall bone quality is determined by its structural and material properties, such as bone mass, geometry, architecture and composition of the bone (Einhorn 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The contrast advantage for phase, i.e. the relation between the real and the imaginary parts of the refractive index, is several orders of magnitude, as pointed by the pioneer in the field, U. Bonse, decades ago [17].…”
Section: Phase-contrast Imaging Using Hard X Raysmentioning
confidence: 99%
“…2 Therefore, researchers estimated that phase-contrast tomography could reach a hundred to thousand times greater sensitivity than absorption-contrast tomography. 3,4 Pioneering tomography studies with hard X-rays revealed that not only the widely used absorption-contrast and the newer phase-contrast imaging techniques provide complementary information but also phase imaging yields a substantially better contrast-to-noise ratio (CNR) than absorption. During the last two decades, high-resolution tomography in the phase-contrast mode has enabled the visualization of individual cells 5 and even sub-cellular details 6,7 in the post mortem human brain.…”
mentioning
confidence: 99%